2018
DOI: 10.1103/physreve.98.022208
|View full text |Cite
|
Sign up to set email alerts
|

Lévy flights on a comb and the plasma staircase

Abstract: We formulate the problem of confined Lévy flight on a comb. The comb represents a sawtoothlike potential field V(x), with the asymmetric teeth favoring net transport in a preferred direction. The shape effect is modeled as a power-law dependence V(x)∝|Δx|^{n} within the sawtooth period, followed by an abrupt drop-off to zero, after which the initial power-law dependence is reset. It is found that the Lévy flights will be confined in the sense of generalized central limit theorem if (i) the spacing between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…From a scientific perspective, the nonlinear dynamics of the plasma staircase occupies an interesting niche where microscale and mesoscale nonlinearities can appear on an equal footing [3,4]. From a practical perspective, the periodic dynamical patterning due to the plasma staircase offers a unique environment to control the avalanche activity by fine tuning the shape and the radial positions of the barriers [4,7]. These practical aspects are dictated by the understanding that the avalanche transport may have a deteriorating effect on the confinement properties of thermal plasma and charged fusion products [8,9], while significant losses could be detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…From a scientific perspective, the nonlinear dynamics of the plasma staircase occupies an interesting niche where microscale and mesoscale nonlinearities can appear on an equal footing [3,4]. From a practical perspective, the periodic dynamical patterning due to the plasma staircase offers a unique environment to control the avalanche activity by fine tuning the shape and the radial positions of the barriers [4,7]. These practical aspects are dictated by the understanding that the avalanche transport may have a deteriorating effect on the confinement properties of thermal plasma and charged fusion products [8,9], while significant losses could be detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…In magnetised plasma experiments, a predator–prey system exists with avalanches (strong driver of transport) and zonal flows (sheared flows that decorrelate turbulent eddies reducing transport). It has been suggested that an Fractional Fokker–Planck Equation on a comb-like potential background can be applied where meso-scale transport events (avalanching) occurs in between regions of strong zonal flow activity (see Milovanov and Rasmussen [ 55 ]). This method is straightforward for applications in this setting; by assuming the used potential in between the zonal flow regions, it is suggested that the potential should be of degree 4 (or higher), as has been used here.…”
Section: Discussionmentioning
confidence: 99%
“…A derivation using transition probabilities in reciprocal space has been obtained in Refs. [50,51]. As is well known, the Riesz operator in Eq.…”
Section: A Continuous Time Random Walks In Wave Number Spacementioning
confidence: 97%
“…which corresponds to the elusive gray swans in the vocabulary of Ref. [51]. The gray swans [51] are a specific type of large-amplitude events [55] that occur at the border of localization-delocalization in complex systems.…”
Section: B Self-organization Without Criticalitymentioning
confidence: 99%
See 1 more Smart Citation